Occlusal Analysis and Management of a Patient with Various Symptoms of Unknown Etiology: A Case Report - Torii, Kengo (British Journal of Healthcare and Medical Research, 2024)
A patient who visited the clinic complaining of tooth hypersensitivity reported various other symptoms during the interview, and an occlusal examination revealed that the patient's habitual occlusal position was slightly off from the muscular position. After adjusting the occlusal position to match the muscular position, the patient's headache, tinnitus, stiff shoulder and vertigo disappeared.